2022
DOI: 10.3390/ijerph192315571
|View full text |Cite
|
Sign up to set email alerts
|

Using Daily Stretching to Counteract Performance Decreases as a Result of Reduced Physical Activity—A Controlled Trial

Abstract: There are many reasons for reduced physical activity leading to reduced maximal strength and sport-specific performance, such as jumping performance. These include pandemic lockdowns, serious injury, or prolonged sitting in daily work life. Consequently, such circumstances can contribute to increased morbidity and reduced physical performance. Therefore, a demand for space-saving and home-based training routines to counteract decreases in physical performance is suggested in the literature. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Assuming every training program to be effective in untrained populations, the consistent positive direction of the effects for all included tests included by Kokkonen et al (2007) seems not surprising. Nevertheless, even though some studies showed significant strength increases ( Kokkonen et al, 2007 ; Warneke et al, 2022d ), overall, static stretching seems not to induce a sufficient stimulus to enhance jumping and sprinting performance.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Assuming every training program to be effective in untrained populations, the consistent positive direction of the effects for all included tests included by Kokkonen et al (2007) seems not surprising. Nevertheless, even though some studies showed significant strength increases ( Kokkonen et al, 2007 ; Warneke et al, 2022d ), overall, static stretching seems not to induce a sufficient stimulus to enhance jumping and sprinting performance.…”
Section: Discussionmentioning
confidence: 92%
“…Eight studies exclusively examined jumping performance ( Hunter and Marshall, 2002 ; Yuktasir and Kaya, 2009 ; Donti et al, 2021 ; Ikeda and Ryushi, 2021 ; Nakamura et al, 2021 ; Panidi et al, 2021 ; Alipasali et al, 2022 ; Warneke et al, 2022d ), two studies ( Rodriguez Fernandez et al, 2016 ; Alipasali et al, 2019 ) only sprint performance. Since four studies assessed both jumping and sprinting performance ( Kokkonen et al, 2007 ; Bazett-Jones et al, 2008 ; Hadjicharalambous, 2016 ; Barbosa et al, 2020 ), the results regarding jumping performance from 12 studies and sprinting results from six studies were examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the investigated stretch training could be seen as an alternative method enhancing flexibility and strength capacity or reduce atrophy of the muscle. Thus, stretching can be assumed to counteract the effects of reduced physical activity, e.g., when long times of sitting at work are mandatory or because of pandemic lockdowns (44) or muscular imbalances (45). Nevertheless, because there is limited literature investigating the effects of long-lasting static stretching interventions on morphological and functional parameters, further research is required to evaluate the transferability to sport-specific performance parameters and its applicability in clinical settings since to this point, the practical application in those fields of interest remains speculative.…”
Section: Discussionmentioning
confidence: 99%